Local and Global Existence of Solutions of the Ginzburg-Landau Type Equations (Journal of Partial Differential Equations, 2007)
This paper is devoted to studying the initial value problem of the Ginzburg-Landau type equations. We treat the case where the nonlinear interaction function is a general continuous function, not required to satisfy any smoothness conditions. Local and global existence results of solutions of the problem are given. Decay estimates are also shown.